AN IMPLICATION OF METAPHORS FOR CONSTRUCTING IDEOLOGIES IN ARUNDHATI ROY'S MY SEDITIOUS HEART - Ayra Tariq; Syeda Beenish Fatima Naqvi; Tanzeela Zahra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The metaphorical structure of Arundhati Roy's book My Seditious Heart was the subject of the current study. The conceptual notion of metaphor served as the research approach for this investigation. The authors of this hypothesis are Lakoff and Johnson (2003). The main goals of this study were to identify the writer's secret identity and to examine conceptual metaphors. Finding out what kinds of conceptual metaphors were employed in the book My Seditious Heart was the study's main goal. We discovered 18 conceptual metaphors. three are an orientational metaphor, six were ontological metaphors, and ten were structural metaphors. The author sociohistorically illustrated the ideology that underlies these conceptual metaphors. She expertly revealed the history of the subcontinent and exposed Indians through metaphorical building.